SOCIAL-EMOTIONAL HEALTH, PERSEPSI TERHADAP SCHOOL CLIMATE, DAN PSYCHOLOGICAL SENSE OF SCHOOL MEMBERSHIP PADA SISWA SEKOLAH DASAR - Nur Widiasmara; Ranti Ambarsari; Elan Zacky Faried (Departemen Psikologi Universitas Pendidikan Indonesia, 2021)
Abstract Emotional and social health are important things for students in schools. This study aims to determine how the role of psychological sense of school membership as a mediator variable how the perception of school climate affects social-emotional health among elementary school students. This study involved 132 students in grades 4 - 6 in Sleman and Yogyakarta, consisting of 84 male students and 48 female students with student ages ranging from 8 - 16 years. The research instruments used the Social Emotional Health Survey-Primary School Sclae (Furlong et al., 2013), The Psychological Sense of School Membership (PSSM) Scale (Goodenow, 1993), and the School Climate Survey: Elementary (La Salle, et al., 2016). Analysis of the data used the PROCESS analysis technique with the help of SPSS for windows version 25. The results of the hypothesis analysis showed that there was an effect of student perceptions on school climate and social-emotional health mediated by psychological sense of school membership in elementary school students in Sleman and Yogyakarta where the coefficient is 0.48 with p 0.00, so the hypothesis is accepted. This shows that psychological sense of school membership can be a mediator on the influence of students' perceptions of the school climate and social-emotional health Abstrak Kesehatan emosi dan sosial merupakan hal yang penting bagi siswa di sekolah. Penelitian ini bertujuan untuk mengetahui bagaimana peran psychological sense of school membership sebagai variabel mediator bagaimana pengaruh persepsi terhadap school climate terhadap social-emotional health pada siswa sekolah dasar di Sleman dan Yogyakarta. Penelitian ini melibatkan 132 siswa kelas 4 - 6, terdiri dari 84 siswa laki-laki dan 48 siswa perempuan dengan usia siswa berkisar dari 8 – 16 tahun. Instrumen penelitian yang digunakan dalam penelitian ini adalah Social Emotional Health Survey-Primary School Sclae (Furlong dkk., 2013), The Psychological Sense of School Membership (PSSM) Scale (Goodenow, 1993), dan School Climate Survey: Elementary (La Salle, dkk., 2016). Analisis data yang digunakan dalam penelitian ini menggunakan teknik analisis PROCESS dengan bantuan SPSS for windows versi 25. Hasil analisis hipotesis menunjukkan bahwa ada pengaruh persepsi siswa terhadap school climate dan social-emotional health yang dimediasi psychological sense of school membership pada siswa sekolah dasar di Sleman dan Yogyakarta dimana koefisien yaitu 0.48 dengan p 0.00, sehingga hipotesis diterima. Hal ini menunjukkan bahwa psychological sense of school membership dapat menjadi mediator pada pengaruh persepsi siswa terhadap school climate dan social-emotional health.